Οι νεοελληνικές τύχες του Αλκιβιάδη ως το τέλος του 19ου αιώνα - Αθήνη, Στέση (Σύγκριση/Comparaison/Comparison, 2016)
The beginning of the closer acquaintance of Modern Greek literature with Alcibiades’ forceful personality is located during the years of Greek Enlightenment, with the discovery of the world of History and the “return to the antiquity” through foreign texts, translated into Greek. Nevertheless, Alcibiades’ appearance as a literary character was delayed compared with his reach European literary fortunes. Alcibiades appears in 1837 through Alcibiades byAugustusGottliebMeissner, a translated “bildungsroman” from German, and half a century later through a second translation, from Italian this time, the homonymous FelicioCavallotti’s historical drama (1889). Examining closely these two texts and considering their presence in the source literatures as well as the terms of their reception in Greek it is concluded that Socrates’ disciple array with literary raiment served the ideological schema aiming at the strengthening of the relations between Modern Greek culture and antiquity and simultaneously the European family.